Dicuil's De cursu solis lunaeque: Translation and commentary - Schweizer, Christian Gregor (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2023)
Between 814 and 818, the Irish scholar Dicuil wrote five untitled books for the Carolingian Emperor Louis the Pious (778-840). This thesis provides the first textual analysis of this work in its entirety and a full translation, making an important early medieval source readily accessible for the first time and laying the foundations for future research. Based on the state of research on Dicuil and his works, the thesis outlines some desiderata and addresses the most urgent ones. The first concerns our understanding of the very nature of this work. Until now, it has been commonly understood to be some kind of astronomical or computistical textbook. In a detailed study of its structure and Dicuil's own references to its purpose, enhanced by a survey of crucial content and contexts, this view is here revised by demonstrating that it was not designed as a cohesive text. Dicuil combined three original showpieces of his skills in computus, the quadrivium, and poetics in 814, in order to convince his new patron Louis of his qualifications and loyalty. He added a similar gift in 815, providing sequels to the three parts of Book I. In 816, he wrote two books focusing on a highly advanced analysis of the Easter cycle, because of a very special combination of imminent calendrical events. Later, Dicuil added two afterthoughts, constituting Book V. Only in 825 did he use a common description for the five books: 'De cursu solis lunaeque'. This is a much more suitable label than the misleading modern name 'Liber de astronomia', and is therefore chosen as a new title. The analysis of the manuscript tradition results in similarly significant findings: Tours, BM, MS 803 and its displaced ending, Paris, BnF, MS NAL 1645, are clearly demonstrated to be a more complete and reliable textual witness than Valenciennes, Médiathèque Simone Veil, MS 404, on which the most complete transcription to date is based. While the only substantial lacuna in the Tours/Paris manuscript is demonstrated to be caused in modern times by the disappearance of two folios, more omissions can be found throughout the codex in Valenciennes. The best explanation is that a very active copyist revised the text, deciding not to copy explicit references to pagan sources and other passages that were regarded as problematic or superfluous. The so far mostly unedited witness in Tours and Paris is more complete, closer to Dicuil's text, and therefore essential for establishing the Latin text. In addition, even a combination of the three previous editions would not provide a complete text. Two, indeed, are mere transcripts, and highly problematic ones. In consequence, a new edition is essential for a dependable full translation, and is therefore provided as an appendix, facing the translation. As outlined in the chapter on its principles, the present edition is based on all codices, with those in Tours and Paris being used as the 'Leithandschrift'. All relevant textual variants are noted in the critical apparatus, because the revised version in Valenciennes is by itself a highly interesting source on editorial interventions and on the reception of classical knowledge in the `Carolingian Renaissance'. The edition also has a biblical and source apparatus, but as the work is highly original, it almost never refers to sources directly or quotes substantial passages verbatim. Concise abstracts of the content are provided in the margins of the edition, providing an essential key to understanding and navigating the text. In addition to these abstracts and the introductory commentary, the translation is supported by short commentaries in parentheses and in footnotes, making this complicated text more accessible and providing essential background information. Some stylistic features and technical terms employed in the text are discussed beforehand in the outline of the principles applied in the translation, thus also supplying a short overview of particularly interesting traits of Dicuil's language and style. The most important technical terms are additionally introduced in a glossary, which is, therefore, not only another important help for accessing the text, but also an outline of Dicuil's computistical customs, innovations, and technical language. Further tools for accessing and analysing the text are provided in four tabular appendices.
APPROVED
Keywords: Dicuil; Computus; Carolingian Renaissance; Louis the Pious; Medieval Science; Medieval Latin Literature; Poetry; quadrivium